2020
DOI: 10.3390/pathogens9030167
|View full text |Cite
|
Sign up to set email alerts
|

The Carrier Conundrum; A Review of Recent Advances and Persistent Gaps Regarding the Carrier State of Foot-and-Mouth Disease Virus

Abstract: The existence of a prolonged, subclinical phase of foot-and-mouth disease virus (FMDV) infection in cattle was first recognized in the 1950s. Since then, the FMDV carrier state has been a subject of controversy amongst scientists and policymakers. A fundamental conundrum remains in the discordance between the detection of infectious FMDV in carriers and the apparent lack of contagiousness to in-contact animals. Although substantial progress has been made in elucidating the causal mechanisms of persistent FMDV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 151 publications
(209 reference statements)
0
66
0
Order By: Relevance
“…Small amounts of residual non-structural proteins may still be present in traditional FMD vaccines, resulting in some animals with false positive results, especially if multiple revaccinations are required due to the inherent short duration of immunity of conventional vaccines (20)(21)(22)(23)(24)(25)(26). Fourth, traditional FMD vaccines may not fully protect animals from persistent infection (10,(27)(28)(29)(30)(31)(32). In a 2016 study by Stenfeldt et al (30), it was shown that neoteric [new or temporally acute (32)] subclinical infection or persistence resulted following challenge in similar percentage of vaccinated and non-vaccinated animals (62% in vaccinated cattle, 67% in non-vaccinated cattle), indicating that vaccination with traditional vaccines has little impact on the carrier state (30,33,34).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small amounts of residual non-structural proteins may still be present in traditional FMD vaccines, resulting in some animals with false positive results, especially if multiple revaccinations are required due to the inherent short duration of immunity of conventional vaccines (20)(21)(22)(23)(24)(25)(26). Fourth, traditional FMD vaccines may not fully protect animals from persistent infection (10,(27)(28)(29)(30)(31)(32). In a 2016 study by Stenfeldt et al (30), it was shown that neoteric [new or temporally acute (32)] subclinical infection or persistence resulted following challenge in similar percentage of vaccinated and non-vaccinated animals (62% in vaccinated cattle, 67% in non-vaccinated cattle), indicating that vaccination with traditional vaccines has little impact on the carrier state (30,33,34).…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, traditional FMD vaccines may not fully protect animals from persistent infection (10,(27)(28)(29)(30)(31)(32). In a 2016 study by Stenfeldt et al (30), it was shown that neoteric [new or temporally acute (32)] subclinical infection or persistence resulted following challenge in similar percentage of vaccinated and non-vaccinated animals (62% in vaccinated cattle, 67% in non-vaccinated cattle), indicating that vaccination with traditional vaccines has little impact on the carrier state (30,33,34).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, FMD-free regions must consider the existence of carriers when responding to incursions. Additionally, neoteric subclinical infection is indistinguishable from persistence under field conditions, and may pose a greater threat of transmission (5,42). Although the role of persistently infected animals in FMDV epidemiology remains controversial, persistently infected animals are known to carry virus in a form that is directly infectious to susceptible animals (15).…”
Section: Discussionmentioning
confidence: 99%
“…Although mortality is usually low, the high morbidity has an important economic impact due to decreased production, regional quarantine practices, and trade restrictions (3,4). The existence of prolonged asymptomatic persistent infection (carrier state) in ruminants has practical implications in FMDV-endemic regions that are distinct from management practices in regions striving to regain FMD-free status after an outbreak (5). Appropriate practices for management of carriers have not been established in either context.…”
Section: Introductionmentioning
confidence: 99%
“…Typical FMD clinical signs include fever and the appearance of vesicular lesions on the tongue, mouth, feet, and teats. Among ruminants that recovered from the disease, a relatively large number become asymptomatic virus carriers ( 2 , 3 ), although it is not clear what is the contribution of these carrier animals to disease transmission in nature ( 4 ). The World Organization for Animal Health (OIE) lists FMD as a reportable disease and therefore, by law, participating nations are required to inform the organization about all FMD outbreaks.…”
Section: Introductionmentioning
confidence: 99%